QuaSiMo: A composable library to program hybrid workflows for quantum simulation. Issue 4 (29th October 2021) - Nguyen, Thien; Bassman, Lindsay; Lotshaw, Phillip C.; Lyakh, Dmitry; McCaskey, Alexander; Leyton‐Ortega, Vicente; Pooser, Raphael; Elwasif, Wael; Humble, Travis S.; de Jong, Wibe A.
Abstract: A composable design scheme is presented for the development of hybrid quantum/classical algorithms and workflows for applications of quantum simulation. The proposed object‐oriented approach is based on constructing an expressive set of common data structures and methods that enables programming of a broad variety of complex hybrid quantum simulation applications. The abstract core of the scheme is distilled from the analysis of the current quantum simulation algorithms. Subsequently, it allows synthesis of new hybrid algorithms and workflows via the extension, specialisation, and dynamic customisation of the abstract core classes defined by the proposed design. The design scheme is implemented using the hardware‐agnostic programming language QCOR into the QuaSiMo library. To validate the implementation, the authors test and show its utility on commercial quantum processors from IBM and Rigetti, running some prototypical quantum simulations.